Dengue Virus NS1 Protein as a Diagnostic Marker: Commercially Available ELISA and Comparison to qRT-PCR and Serological Diagnostic Assays Currently Used by the State of Florida - Ambrose, J.H.; Sekaran, S.D.; Azizan, A. (Hindawi Publishing Corporation, 2017)
Background. The proper management of patients infected with dengue virus requires early detection. Here, real-time molecular assays have proven useful but have limitations, whereas ELISAs that detect antibodies are still favored but results are obtained too late to be of clinical value. The production of DENV NS1 peaks early during infection and its detection can combine the advantages of both diagnostic approaches. Methods. This study compared assays currently used for detecting DENV infection at the Florida Department of Health including anti-DENV IgM and IgG ELISAs as well as qRT-PCR, against a commercially available DENV NS1 ELISA. These comparisons were made among a group of 21 human sera. Results. Nine of 14 (64.3%) DENV qRT-PCR+ samples were also DENV NS1+. Interestingly, the 5 NS1− samples that were qRT-PCR+ were additionally IgM− and IgG+ suggesting a nonprimary infection. Compared to qRT-PCR, the NS1 assay had a sensitivity of 64.3%, specificity 100%, PPV of 100%, and NPV of 58.3%. Conclusions. The NS1 ELISA performed as expected in known DENV qRT-PCR+ samples; however negative NS1 results for qRT-PCR+ and IgG+ sera seemingly reduced the usefulness of the NS1 ELISA for nonprimary cases. We therefore conclude that diagnosis obtained via DENV NS1 ELISA deserves further investigation.